113k views
0 votes
I'm stuck yet .......

I'm stuck yet .......-example-1
User Ajamu
by
6.2k points

2 Answers

4 votes

Answer:

Choice C is correct. (g o f)(3) = 49

Explanation:

We have given two functions:

f(x) = 3x-2

g(x) = x²

We have to find (g o f)(3) = ?

(g o f)(x) = g(f(x))

putting values in above formula we get,

(g o f)(x) = (3x-2)²

(g o f)(x) = 9x²+4-12x

Now, putting x = 3 in above equation we get,

(g o f)(3) = 9(3)²+4-12(3)

(g o f)(3) = 9(9)+4-36

(g o f)(3) = 81+4-36

(g o f)(3) = 49 is the answer.

User Hobeau
by
6.3k points
2 votes

Answer:

49 choice C is the correct solution

Step-by-step explanation:

The composite function, (g o f) simply means we substitute the function f(x) in place of x in the function g(x).

since g(x) =x^2, (g o f) =(f(x))^2 = (3x-2)^2.

The final step is to substitute x=3 in the last expression which yields 49.

User Raditya Kurnianto
by
6.0k points